STRATEGI KOMUNIKASI PEMASARAN PT BARUGA ASRINUSA DEVELOPMENT DALAM MENINGKATKAN KONSUMEN DI KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This study aims to find out the strategy of PT. Baruga Asrinusa Development in increasing consumers in Makassar City. To find out the techniques for using communication media in reaching the target consumers of PT. Baruga Asrinusa Development. This research uses a type of qualitative research with a communication science approach, especially related to marketing communication. This approach is carried out by the researcher to analyze the work process or strategic steps that have been planned to achieve the goals by the members of PT. Baruga Asrinusa Development in increasing the number of consumers. Data was collected through observation, interviews, and documentation. Data analysis is carried out by data reduction, data presentation, and conclusions drawn. The results of the study show that PT. Baruga Asrinusa Development Makassar implements a marketing communication strategy by: 1) bringing together multiple integrated communication channels; 2) leveraging analytics data to tailor messaging; and 3) integrating marketing and sales teams. This strategy ensures consistency of messaging across platforms and tailoring promotions according to consumer preferences, as well as improving team coordination. 4) Periodic evaluations are also carried out to maintain the effectiveness and adaptation of promotions to market changes. Then the use of communication media by PT. Baruga Asrinusa's reach out to consumers involves 1) targeting the right audience 2) choosing the right media platform. The use of effective channels such as Instagram, which allows for aesthetically pleasing product presentations, as well as collaboration with influencers. Facebook is used for segmented ads and analytics that help with promotional customization, while TikTok attracts the younger generation with entertaining short videos. and the use of honest and transparent media to build trust. This has succeeded in creating a strong connection with consumers, expanding marketing reach, and driving positive purchase decisions.